Post kidney transplant infections with special reference to cytomegalovirus - Tiwari, Jai Prakash; B., Prashanth; A. V., Vinay Kumar (International Journal of Research in Medical Sciences, 2023)
Background: The burden of infectious disease is high among kidney transplant recipients because of concomitant immunosuppression. Methods: Study was a retrospective and prospective cohort study. The study was conducted for a period of 12 months and 30 transplant recipients were included. Results: Males comprised 86.66% of the study population. The mean age of the recipients was 37.96 years. UTI was the most common post-transplant infection observed in 15 patients (50%) of 30 patients. E. Coli infection was most predominant (50%) causing UTI. 5 patients (16.66%) in this study developed tuberculosis after renal transplantation. Two patients (6.66%) developed CMV infection in the study. Two patients (6.66%) developed COVID-19 infection in the study. Two patients (6.66%) developed herpes infection post-transplant. One patient (3.33%) in the study developed cryptococcal meningitis. One patient (3.33%) developed hepatitis C after 18 years of transplant. One patient (3.33%) developed hepatitis B after 10 years of transplant. Three patients (10%) developed lower respiratory tract infection and developed acute respiratory distress. Three patients (10%) had developed acute graft rejection within first year after transplantation. There are total of 13 deaths (43.33%) among 30 patients all of which were secondary to infections. Total of 4 patients among the 13 deaths had chronic graft rejection. Most common cause of death was tuberculosis (38.46%) followed by UTI (23%) and Lower respiratory tract infection (23%). Conclusions: The incidence of infections is relatively higher in kidney transplant recipients when compared to general populations due to immunosuppression.